Pendidikan Kewarganegaraan dalam Perspektif Society 5.0: Membangun Warga Negara Humanis-Teknologi: Citizenship Education in the Perspective of Society 5.0: Building Humanistic-Technological Citizens - Ahmad Muhamad Mustain Nasoha; Muhamad Febrian; Muhamad Adip Salikin; Faiq Gibran Abdullah; Muhammad Nadhif Mirzaq (Litera Academica Publishing, 2025)
The development of information technology is currently reaching all areas of people’s lives, including education. In the era of the industrial revolution 4.0 required three literacies namely data literacy, human literacy, and technological literacy. Learning in the revolutionary era 4.0 can apply hybrid / blended learning and Case-base Learning. Even education in the era of society 5.0, allows students or students in learning activities side by side with robots that have been designed to replace the role of educators. So what about the education system in Indonesia? This paper examines the readiness of Indonesian education in welcoming the era of society 5.0. Thus, activists and education stakeholders get a picture of the urgency of the presence of technology era society 5.0 in the world of education.